Telerehabilitation in speech-language therapy as exemplified by aphasic patients. A research review - Manicki, Krystian (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The present paper discusses application of telerehabilitation services in speech therapy management in aphasic adults. The author presents theoretical issues related to the specifics of therapeutic effects of at a distance approach and indicates its recipients, focusing on neurological patients with language difficulties. Further on, the author reviews the selected studies on telerehabilitation used in diagnoses and therapies of aphasic speech disorders.